Arts education transfer – thirty years’ debate for justifying arts - Mikko Ketovuori; Kaarina Marjanen (Spain, 2022)
The last thirty years, widespread concern about the role of arts in education has created demand for transfer research. The question has mainly been, how beneficial the arts are for students. Quite recently, in the field of music education, the first meta-analyses of the issue have been released (Sala & Gobet 2020; Cooper 2020). The outcome of the research has been proved also in earlier papers concerning other art forms (Burton, Horowitz & Abeles 2000), and hence meets the expectations of the average critical researcher. Direct transfer is a myth busted, which ought to have a significant influence on how these issues are discussed in the field of arts education from now on. In this paper, transfer research phenomenon is discussed and put in its historical context, as well as, some recommendations for another justification of arts in education is suggested.
Conference Proceedings CIVAE 2020 : 2nd Interdisciplinary and Virtual Conference on Arts in Education, October 28-29, 2020